The Impact of Job Flexibility, Workload, and Self-Efficacy on Work–Life Balance: The Mediating Role of Technology Effectiveness and Organizational Support, and the Moderating Role of Leadership Style among Remote Knowledge Workers - Ghalbi, Mansour; Zolfaghari, Alireza; Pirani, Zabih (KMAN Counseling & Psychology Nexus, 2025)
The purpose of this study is to examine the impact of job flexibility, workload, and individual self-efficacy on work–life balance, considering the mediating role of technology effectiveness and organizational support, as well as the moderating role of leadership style among remote knowledge workers. This research is applied in nature and adopts a descriptive–correlational method. The statistical population consisted of 196 remote employees working in startup companies in Tehran. Using convenience sampling and G*Power software, a sample size of 111 was determined. Data were collected through a questionnaire, and path analysis was conducted using PLS version 3 software. The results indicated that organizational support mediates the relationship between workload and work–life balance (R²=0.542, p=0.000), as well as between individual self-efficacy and work–life balance (R²=0.582, p=0.000). Furthermore, technology effectiveness mediates the relationships between job flexibility (R²=0.698), workload (R²=0.745), and self-efficacy (R²=0.685) with work–life balance (all with p=0.000). The moderating role of leadership style was also confirmed (R²=0.639, p=0.000). Based on the findings, it is recommended that training programs be designed and implemented to enhance self-efficacy and increase job flexibility for remote employees.